Pollution and its Impacts on the South American Cryosphere. Issue 12 (16th December 2015) - Molina, Luisa T.; Gallardo, Laura; Andrade, M.; Baumgardner, D.; Borbor‐Córdova, M.; Bórquez, R.; Casassa, G.; Cereceda‐Balic, F.; Dawidowski, L.; Garreaud, R.; Huneeus, N.; Lambert, F.; et al.
Abstract: This article is a review of the science goals and activities initiated within the framework of theP ollution and itsI mpacts on theS outhA mericanC ryosphere (PISAC) initiative. Air pollution associated with biomass burning and urban emissions affects extensive areas of South America. We focus on black carbon (BC) aerosol and its impacts on air quality, water availability, and climate, with an emphasis on the Andean cryosphere. BC is one of the key short‐lived climate pollutants that is a topic of growing interest for near‐term mitigation of these issues. Limited scientific evidence indicates that the Andean cryosphere has already responded to climate change with receding glaciers and snow cover, which directly affect water resources, agriculture, and energy production in the Andean region of South America. Despite the paucity of systematic observations along the Andes, a few studies have detected BC on snow and glaciers in the Andes. These, in addition to existing and projected emissions and weather patterns, suggest a possible contribution of BC to the observed retreat of the Andean cryosphere. Here we provide an overview of the current understanding of these issues from scientific and policy perspectives, and propose strategic expansions to the relevant measurement infrastructure in the region. Key points: A review of black carbon pollution impacts on the Andean cryosphere is presented The lack of observations in the Andean region hampers the understanding of glacier retreat Few mitigation measures relevant to short‐lived pollutants have been adopted in the region